Ethnographic bibliography of North America - Murdock, George Peter 1897-1985 (Human Relations Area Files, 1960)
Includes works on linguistics, art, anthropology, archaeology, etc.
Keywords: Eskimo's; Ethnologie - Amérique du Nord - Bibliographie; Indianen; Indiens d'Amérique - Amérique du Nord - Bibliographie; Indianer; Ethnology -- North America -- Bibliography; Indians of North America -- Bibliography; Indians, North American -- North America -- Bibliography; Eskimo; Ethnologie; Nordamerika; USA; Bibliografie